Successful management of high urogenital sinus in an adult female: Case report - Gamal Ghoniem; Nardeen Magdy Samaan; Mohamed Samir; Muhammed A. Moukhtar Hammad; Ashraf G. Fahmy (Continence Reports)
This case report presents the successful management of high urogenital sinus (UGS) in a 21-year-old female using a modified Anterior Sagittal Transrectal Approach (ASTRA). The patient, with a history of painful cyclic hematuria and delayed menarche, was initially misdiagnosed with a transverse vaginal septum. Diagnostic clarity was achieved through cystourethroscopy, revealing a single external meatal opening indicative of UGS. The modified ASTRA technique, including a rectum-sparing approach, was employed to correct the anomaly. Preoperative administration of leuprolide acetate helped reduce the risk of postoperative infections and complications. Postoperative care included serial vaginal dilatations to prevent stenosis, resulting in no complications or need for further surgical interventions at 12-month follow-up. This case highlights the importance of a multidisciplinary approach and the potential of the modified ASTRA technique in managing high UGS in adult patients. Further research to validate these findings in a larger cohort could be difficult because of rarity to miss the diagnosis in adult females.